HUBUNGAN BEBAN KERJA DENGAN PRODUKTIVITAS KERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RSUD HARAPAN DAN DOA KOTA BENGKULU - Maydinar, Dian Dwiana; Sasmita, Fatima Nuraini (STIKES Syedza Saintika Padang, 2023)
One of effort for produce the good quality working is increasing working productivity. The low productivity in hospital able to make decreasing the number of patient becauce low of service aquality. Good or not of nurse productivity is depend on variour factor either work load. This study purosed as to know relationship between work load and working productivity of nurse associate at inpatient room of harapan dan doa hospital Bengkulu city, and has conducted from mei 31 to june 15 2023. The type of study was Quantitative research by cross-sectional design. The population of this study were all of nurse associate that working at inpatient room of harapan dan doa hospital Bengkulu city ar many as 50 respondents. The sample of this study were taken by total sampling technique ar many as 50 respondents. The data has used by primary and secondary data, data analisis has used by univariate and bivariate analysis. The resulded of this study showed from 50 nurse associate obtraired that 10 respondents (20%) have heavy work load and 40 respondens (80%) have low work load and working productivity obtraired that working productivity of nurse was not good, amounting to 11 nurse (22%), working productivity of nurse is good ar many as 39 respondents (78%). Bared on the resulded of fisher’s exact tes obtained that the p-value was 0.000. because the p-value < 0,05 , so that Ha was accepted and Ho was rejected. So that able to conclution that there is siqnificant relactionship between work load and working productivity of nurse associate at inpatient room of harapan dan doa hospital., Bengkulu city. Keywords : Working Productivity, Work Load, Nurse Associate